Pelatihan Safety Management System bagi Pegawai Unit Penyelenggara Bandar Udara Gusti Syamsir Alam Kotabaru - Wildan Nugraha; Direstu Amalia; Asep Muhamad Soleh; Fitri Masitoh; Anton Abdullah (Darmabakti: Jurnal Inovasi Pengabdian dalam Penerbangan, 2020)
Aviation Safety Management System (SMS) is mandatory for 5 flight operators, one of which is the airport as mandated by the International Civil Aviation Organization (ICAO Doc 9859, 2019). Palembang Aviation Polytechnic as a work unit in charge of providing training in aviation, through community service activities, implementing Safety Management System Training for 25 participants with different work backgrounds from UPBU Gusti Syamsir Alam, Kotabaru Regency, South Kalimantan Province. This training is given using lecture methods, project-based learning and group presentations. The training provides increased understanding in the field of the Safety Management System with the result of obtaining a comprehensive exam with 84.96 as the average score. 36% of participants successfully passed with honors, and 64% with Good honors.